2016
DOI: 10.3762/bjoc.12.63
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective amine-thiourea-catalysed sulfa-Michael/nitroaldol cascade approach to 3,4,5-substituted tetrahydrothiophenes bearing a quaternary stereocenter

Abstract: SummaryAn investigation on the stereoselective cascade sulfa-Michael/aldol reaction of nitroalkenes and commercially available 1,4-dithiane-2,5-diol to 3,4,5-substituted tetrahydrothiophenes, bearing a quaternary stereocenter, is presented. A secondary amine thiourea derived from (R,R)-1,2-diphenylethylamine was found to be the most effective catalyst when using trans-β-methyl-β-nitrostyrenes affording the heterocyclic products in good yields and moderate stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…[198] Thea uthors also established ap arallelr elationship between the diastereoselective ratios andc omputed thermodynamic stability of the different diastereomers of tetrahydrothiophenes 516 in toluene. [198] Thesea uthors also achieved ad omino double Michael reactionb etween a-cyano-a,b-unsaturated ketones 518 and tert-butyl trans-4-mercapto-2-butenoate (trans-519a,R 3 = t-Bu) using the same amine thiourea catalyst 517,w hich led to the formation of tetrahydrothiophenes 520 in good yields ands tereoselectivities (Scheme 137, left equation).…”
Section: 213synthesis Of Thia-heterocyclesmentioning
confidence: 95%
See 1 more Smart Citation
“…[198] Thea uthors also established ap arallelr elationship between the diastereoselective ratios andc omputed thermodynamic stability of the different diastereomers of tetrahydrothiophenes 516 in toluene. [198] Thesea uthors also achieved ad omino double Michael reactionb etween a-cyano-a,b-unsaturated ketones 518 and tert-butyl trans-4-mercapto-2-butenoate (trans-519a,R 3 = t-Bu) using the same amine thiourea catalyst 517,w hich led to the formation of tetrahydrothiophenes 520 in good yields ands tereoselectivities (Scheme 137, left equation).…”
Section: 213synthesis Of Thia-heterocyclesmentioning
confidence: 95%
“…[198] Thea uthors also established ap arallelr elationship between the diastereoselective ratios andc omputed thermodynamic stability of the different diastereomers of tetrahydrothiophenes 516 in toluene. [198] Thesea uthors also achieved ad omino double Michael reactionb etween a-cyano-a,b-unsaturated ketones 518 and tert-butyl trans-4-mercapto-2-butenoate (trans-519a,R 3 = t-Bu) using the same amine thiourea catalyst 517,w hich led to the formation of tetrahydrothiophenes 520 in good yields ands tereoselectivities (Scheme 137, left equation). [199] Thea uthors proposed ad ynamic kinetic resolution (DKR)p athwayt hat involvedadomino sulfa-Michael/retro-Michael/Michael reactiont oa ccount for the experimental results,s uch as the isolation of racemicM ichaela dduct 521 and its successful transformation to the diastereoenriched final product 520 under the reaction conditions.…”
Section: 213synthesis Of Thia-heterocyclesmentioning
confidence: 95%
“…The authors observed a dynamic kinetic resolution process that played a role in the high enantioselectivity in the reaction. In the next year, Xu et al employed 1,4-dithiane-2,5-diol (38), the dimer of mercaptoacetaldehyde (39), for the synthesis of enantiopure tetrahydrothiophenes (Scheme 11). [30] For this purpose, chalcones 40 were used as Michael acceptors, and 41, a bifunctional quinine-derived squaramide, was found to be the most efficient catalyst.…”
Section: Bifunctional H-bonding Catalytic Routementioning
confidence: 99%
“…The authors explained the stereochemical outcome of the reaction as shown in Scheme 12. Here also, the thiol of mercaptoacetaldehyde (39) is activated by the tertiary amino group, and the squaramide activation of the carbonyl group of the chalcone leads the Michael addition to take place through intermediate A from the Re-face to generate intermediate B.…”
Section: Bifunctional H-bonding Catalytic Routementioning
confidence: 99%
See 1 more Smart Citation